2019
DOI: 10.1021/acs.chemrestox.9b00134
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Inorganic Arsenic and Lead and Autism Spectrum Disorder in Children: A Systematic Review and Meta-Analysis

Abstract: Inorganic arsenic (iAs) and lead (Pb) rank first and second on the U.S. Environmental Protection Agency’s priority list of hazardous substances. Both are known neurotoxic metals that cause detrimental effects on brain development and lead to deficits in cognitive function and behavioral performance in children. Studies have indicated a potential link between iAs and Pb exposure and a higher risk for autism spectrum disorder (ASD). To provide further insight into whether developmental exposure to iAs or Pb is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…In addition, Mn and Pb were also associated with the severity and characteristics of ASD [ 129 ]. A systematic review and meta-analysis concluded that early life iAS exposure is positively associated with ASD, and the relationship between lead exposure and autism risk is controversial [ 130 ]. Another recent systematic review and meta-analysis indicated that existing evidence supports significant associations between ASD and Al, Cd, and Hg, respectively [ 131 ].…”
Section: Neurological Disorders With Mitochondrial Dysfunction and Oxidative Stressmentioning
confidence: 99%
“…In addition, Mn and Pb were also associated with the severity and characteristics of ASD [ 129 ]. A systematic review and meta-analysis concluded that early life iAS exposure is positively associated with ASD, and the relationship between lead exposure and autism risk is controversial [ 130 ]. Another recent systematic review and meta-analysis indicated that existing evidence supports significant associations between ASD and Al, Cd, and Hg, respectively [ 131 ].…”
Section: Neurological Disorders With Mitochondrial Dysfunction and Oxidative Stressmentioning
confidence: 99%
“…There is a list of 201 industrial chemical agents that have a neurotoxic effect on humans (including Pb and As). They may cause autism and other disorders such as attention deficit, mental retardation, and cerebral palsy [1,16,17,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…In children whose mothers were exposed to As compounds, the following symptoms are observed: difficulty with learning, memory, concentration, cognitive and behavioral disorders. Children exposed to this element may also present the symptoms of retarded development or inhibited physical and mental development [1,5,6,13,23,[29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, inorganic arsenic, cadmium, lead, and mercury are among the ten chemicals/groups of chemicals of major public health concern according to World Health Organization (WHO) [148]. Studies have shown that these metal/metalloids associated with numerous diseases such as development of autism spectrum disorder in children [149], skin pigmentation change and lesions [150], liver and renal diseases [151], neural diseases and anemia [152].…”
Section: Heavy Metal Ion Adsorptions (Metal Ion Removal)mentioning
confidence: 99%